Methodological features of the study of toxicological chemistry - O. I. Panasenko; A. S. Нotsulya; A. A. Safonov; V. P. Buryak; I. V. Melnik; R. O. Sherbyna (Zaporožskij Medicinskij Žurnal)
Methodological features of toxicological chemistry teaching in pharmaceutical faculties of medical institutions according to the Bologna declaration requirements were considered and justified.